G227(P) Liquid detergent capsules are the commonest cause of accidental poisoning in children less than 5 years-old presenting to two UK emergency departments. (25th October 2020) - Dayasiri, MBKC; Peppiatt, J; Bird, C
Abstract : Aims: Despite a global campaign on the dangers presented by liquid detergent capsules (LDC) – which look like sweets to a toddler - young children continue to present to emergency departments with LDC ingestion. We aimed to determine how often LDCs, or 'liquitabs', were the cause of children presenting with accidental poisoning to our two emergency departments. Methods: We performed a retrospective analysis of all children less than 5 years old and presenting between July 2016 and July 2018 with an accidental poisoning to the emergency departments at the John Radcliffe Hospital, Oxford, and the Horton Hospital, Banbury. Children with either deliberate, food or unknown poisoning were excluded. As an audit, the study did not require ethical approval. Results: Among 214 children with accidental poisoning (median age of 2 years, 52.3% male), LDCs were the commonest cause (27 cases, 12.6%), followed by paracetamol (15, 7%) and carbon monoxide (10, 4.7%). There were 103 different substances recorded, with personal care products forming the largest group (110, 51.4%) followed by medications (57, 26.6%). Most children were asymptomatic (173, 80.8%). The commonest symptom was vomiting (22, 10.3%). A quarter had an ECG performed (47, 22%) and 31 (14.5%) children had a blood test. All children were discharged from the emergency department after a period of observation. Conclusion: LDCs were the commonest cause of accidental poisoning in young children presenting to our emergency departments. Healthcare workers should engage with industry to make packaging of LDCs safer to prevent continued presentations by young children with LDC poisoning.